Desenvolvimento e caracterização físico-química e sensorial de fermentados de butiá (Butia odorata) - Bernardi, Gabrieli (2013)
Fruits from different biomes haven been studied as a new alternative to the development of alcoholic fermented beverages besides the traditional grape wine. Jelly palm (butia odorata) is a typical fruit from the southern region of Brazil. This fruit possess a yellow color, fibrous pulp and a sensorial characteristic that combines sweetness with acidity. The aim of this work was the development of a fermented beverage and the study of the compounds responsible for the aroma of the beverage. Microvinifications were conducted at temperatures and 10 and 20 ºC with 7 and 2 days of maceration time. The fermented beverage showed an average value of 11 GL for alcoholic graduation. Total acidity ranged between 0.68% (D2T10) and 1.16% (M7T20) and volatile acidity ranged between 0.06% (D2T10) and 0.11% (M7T20). Residual sugar and pH ranged between 0.93 to 1.29 g/l and from 3.83 to 3.95, respectively. The minor volatile compounds of jelly palm wine were extracted using solid-phase microextraction technique employing a DVB/CAR/PDMS fiber. Ten milliliters of the wine were extracted at 35 °C for 45 minutes, added to 30% NaCl and kept under constant stirring. The volatile fraction was analyzed by GC-FID and GC-MS allowing the identification and quantification of compounds from esters 60 (27), alcohols (15), acids (11), lactones (2), aldehydes (1), ketones (1), terpenes (1). For the higher alcohols and other major volatile compounds, the extraction was performed directly in the static headspace (HS) of the sample. The method used was validated with respect to lineariry (0.991-0.998), sensitivity LOD (0.01-0.5) and LOQ (0.1-1), precision as repeatability (6.5-10.9%) and intermediate precision (7.2-10.3%) and accuracy (86-96%). The evaluation of the jelly palm wine aroma by GC-O showed that the volatile compounds that most contributing to the aroma are, esters (ethyl hexanoate) and alcohols (3-methyl-1-butanol). The acid, hexanoic acid was described as a potential off flavor having a higher concentration in the fermentations at 20 ºC. Sensory analysis showed that the acceptability of the beverages were higher for those fermented at 10 ºC that possess the lower concentrations of the hexanoic acid.